Solar home automation system (electro-mechanical part) - Mohd Radzi, Mohd Rasol (2008)
This project is mainly concerned on development of solar home automation system for electro-mechanical part and integration. The main objective in this project is to give an experience and knowledge for student to make the project and activity successfully. The specific objective of to design the mechanical and electronic part of solar home automation system. This project as model to an application for a real house .This project involve the process of designing the circuit ,mechanical part ,functionality and the manufacturing costs for people using. The material using is solar panel, Perspex, electric components such as diode , battery, lamp, led and switch on/off. In this project have 3 main process .The first process is fabricate the electrical part, the second one process is fabricate the mechanical part and the last one is integrated electrical part and mechanical part. The electrical part need to make a circuit . To generate the electric by solar energy. Mechanical part to make model house. Lastly, two part need to integrate. The results can also significantly reduce the cost and time to market, and improve product reliability and customer confidence.